Urtica dioica (Stinging Nettle): A Comprehensive & Concise Review on its Nutritional Profile and Therapeutic Applications - Aziz, Namra; Vinod, Yadav R.; Sarkar, Dhrubajyoti; Wal, Ankita; Verma, Vaibhav; Wal, Pranay (Current Traditional Medicine, 2024)
Background: A relatively untapped origin of drugs is medicinal plants. Traditional medicine employs Urtica dioica L. to treat a variety of ailments. A plant that produces fresh leaves that are dehydrated and used as a powder or in various forms is gaining popularity as a recent source of very nutritious food. Objective: This review attempts to address its nutritional profile, as well as its bioactive chemical ingredients and known food functional activities, as well as its historical usage in food and medicine. To date, several bioactive chemical components from stinging nettle have been identified, including flavonoids, phenolic and amino acids, fatty acids and carotenoids. Method: A comprehensive analysis of the literature search was conducted. Several databases have been searched using the common terms Urtica dioica, stinging nettle, phenolic compounds and phytochemicals using Scopus, Science Direct, PubMed-Medline and Google Scholar as search engines. Conclusion: The therapeutic potential of Urtica dioica and its disease-preventing strategies are updated in this review article. Also, its classification, chemical composition, nutritive value, and pharmacological activities are enlisted in this review with further future perspectives of Urtica dioica.
Keywords: nutritional profile